Museum exhibition planning and design - Bogle, Elizabeth (AltaMira Press, a division of Rowman and Littlefield Publishers, Incorporated, 2013)
Museum Exhibition Planning and Design is a comprehensive introduction and reference to exhibition planning and design. This book focuses on both the procedural elements of successful planning, like the phases of exhibit design and all associated tasks and issues, and on the design elements that make up the realized exhibit itself, such as color, light, shape, form, space, and building materials.